Priorities for Greening and the Sustainable Development of OECD Member Countries and Ukraine: a Comparative Analysis - Dovgal, Olena; Goncharenko, Nataliia; Reshetnyak, Olena; Dovgal, Georgiy; Danko, Natalia (Comparative Economic Research. Central and Eastern Europe, 2021)
The article focuses on identifying priority areas for greening and sustainable development for OECD countries and Ukraine. They aim to achieve overall progress in the interaction between the economy and the environment. Additionally, the aim is to create prerequisites for encouraging innovation and investment to find new sources of economic growth that are compatible with ecosystems that are capable of recovering from damage. It has been demonstrated that although the global goals of greening economies are relevant for all countries, they must be tailored to the regional and national specificities, as well as each country’s level of economic development. The study used general qualitative and quantitative methods of economic research, including systematic, comparative analysis, methods of logical and statistical analysis, and index method, among others. The applied theoretical and methodological approach allowed us to identify general trends in the development of environmental factors in the OECD countries and Ukraine and their impact on economic growth. Specifically, the study analyzes the current state of affairs and perspectives for greening and sustainable development based on a comprehensive assessment of the level of greening in these economies and the relationship between the internal ecological environment – assessed using the indicators of “green growth” – and their economic development. The article also justifies priorities for greening and sustainable development and suggests practical measures for their implementation. They can serve as a basis for developing a policy of effective environmental management and elaborating a national system of environmentally friendly management and administration.